2008
DOI: 10.1016/j.jadohealth.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Tobacco Abstinence in Adolescent Smokers Compared with Nonsmokers

Abstract: Purpose-Abstinence effects such as nicotine withdrawal and mood changes contribute to the maintenance of cigarette smoking in adult smokers and emerging reports on adolescent smokers suggest they may experience similar subjective effects when deprived. This study aimed to prospectively document tobacco abstinence induced changes during the first 48 hours of abstinence in adolescent smokers compared with nonsmokers, to distinguish effects distinct from typical adolescent lability.Methods-57 adolescent smokers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…As has been shown previously (e.g. Killen et al, 2001; Smith et al, under review), symptoms were relatively mild and few in number with craving being the most notable effect.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As has been shown previously (e.g. Killen et al, 2001; Smith et al, under review), symptoms were relatively mild and few in number with craving being the most notable effect.…”
Section: Discussionsupporting
confidence: 83%
“…In adolescent humans, the nicotine patch may not prevent development of withdrawal symptoms (Killen et al, 2001) and its efficacy has been less conclusively established with adolescent smokers (Hurt et al, 2000; Smith et al, 1996; Hanson et al, 2003; Moolchan et al 2005). Finally, interestingly, although they report withdrawal symptoms, adolescent smokers may in fact only differ from their nonsmoking peers on reports of cravings in response to abstinence (Smith et al, under review; Prokhorov et al 2005). In addition, adolescents’ patterns of tobacco use are likely more highly constrained than those of adults by such factors as school or home rules and regulations (Wiltshire, Amos, Haw, & McNeill, 2005).…”
mentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that nicotine replacement does not prevent the expression of nicotine withdrawal symptoms in adolescent smokers (Killen et al, 2001). Moreover, a recent study directly comparing adolescent smokers to non-smokers found that young smokers only exhibit mild symptoms during withdrawal (anger and craving) that do not appear to be associated with self-reports of dependence or biological markers of cigarette use (Smith et al, 2008a). Another report from this laboratory found that withdrawal symptoms on the quit day were not related to relapse behavior in adolescent smokers (Smith et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…For completeness, however, we briefly review findings relating to adolescent withdrawal. Relative to the adult experience of withdrawal, adolescents experience mild withdrawal symptoms (Smith et al, 2008a). Withdrawal symptoms also seem to be less relevant to promoting relapse during quit attempts in adolescent relative to adult smokers (Smith et al, 2008b).…”
Section: From First Cigarette To Compulsive Usementioning
confidence: 99%